Antecedent and Consequence Model of Trust on Online Fashion Retail (Zalora) - Laili, Fauzia Nur; Wahyudi, Lilik (Universitas Sebelas Maret, 2021)
This study has the purpose to understand the antecedents and consequences of trust in online shopping consumers. The model of three (perceived quality, perceived risk, and trust) increase the intention to purchase on the e-commerce platform.